POWER AND IMPOLITENESS IN THE DEVIL WEARS PRADA MOVIE - Ayu Ratri; Priyatno Ardi (Elite : English and Literature Journal, 2019)
This research examines the types of impoliteness strategies and the purposes of the exercise of power through impolite language in the movie The Devil Wears Prada. This study focuses on two characters, namely Miranda and Emily, who have power relationship in their workplace. The researchers employed qualitative content analysis method. The findings suggest that Miranda used all types of impoliteness strategies. Meanwhile, Emily only used bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. The purposes of Miranda’s exercise of power were to appear as superior, get authority over actions, dominate in a conversation, and to reactivate the power. At the same time, the purposes of Emily’s exercise of power were to appear as superior, to get authority over actions, to emphasize the power hierarchy, and to reactivate the power.Keywords: impoliteness strategies, power, The Devil Wears Prada movieABSTRAKPenelitian ini membahas jenis strategi ketidaksantunan dan tujuan penggunaan kekuasaan melalui bahasa yang tidak santun dalam film The Devil Wears Prada. Fokus penelitian ini pada dua karakter, yaitu Miranda dan Emily, yang memiliki hubungan kekuasaan di tempat kerja mereka. Analisis konten digunakan dalam penelitian ini. Hasil penelitian ini menunjukkan bahwa Miranda menggunakan semua jenis strategi ketidaksantunan. Sementara itu, Emily hanya menggunakan ketidaksantunan secara langsung (bald on record impoliteness), ketidaksantunan positif (positive impoliteness), ketidaksantunan negatif (negative impoliteness), dan sarkasme atau kesantunan semu (sarcasm or mock politeness). Tujuan Miranda menggunakan kekuasaanya adalah untuk tampil superior, mendapatkan otoritas atas tindakan, mendominasi percakapan, dan untuk mengaktifkan kembali kekuaasaan. Tujuan Emily menggunakan kekuasaannya adalah untuk tampil superior, untuk mendapatkan otoritas atas tindakan, untuk menekankan hierarki kekuasaan, dan untuk mengaktifkan kembali kekuasaan.Kata Kunci: strategi ketidaksantunan, kekuasaan, film The Devil Wears Prada